2022
DOI: 10.1002/cbin.11844
|View full text |Cite
|
Sign up to set email alerts
|

ANKHD1 contributes to the malignant phenotype of triple‐negative breast cancer cells

Abstract: Ankyrin repeat and KH domain-containing protein 1, ANKHD1, has been identified as a regulator of signaling pathways and cellular processes of relevance in carcinogenesis. However, the role of ANKHD1 in breast cancer remains unclear.The aim of the present study was to characterize the expression pattern and involvement of ANKHD1 in the malignant phenotype of breast cancer cell lines and to investigate the clinical relevance of ANKHD1 in a breast cancer context. Gene and protein expressions were assessed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The potential functional significance of the nuclear localisation of ANKHD1 remains largely unknown, and there is insufficient evidence as to whether the subcellular localisation is tissue/cell type dependent, although it has been proposed [ 38 ].…”
Section: Subcellular Localisation Of Ankhd1mentioning
confidence: 99%
See 3 more Smart Citations
“…The potential functional significance of the nuclear localisation of ANKHD1 remains largely unknown, and there is insufficient evidence as to whether the subcellular localisation is tissue/cell type dependent, although it has been proposed [ 38 ].…”
Section: Subcellular Localisation Of Ankhd1mentioning
confidence: 99%
“…Colorectal cancer cells show increased levels of ANKHD1 and are associated with an increase in epithelial-to-mesenchymal transition, allowing increased cell mobility, possibly linking ANKHD1 to increased migration and the invasion of cancer cells [ 54 ]. Furthermore, increases in migration and invasiveness of cancer cells demonstrating high expression of ANKHD1 has also been described in hepatocellular carcinoma [ 61 ], breast cancer [ 38 ], non-small-cell lung cancer [ 53 ] and multiple myeloma [ 57 ] cells. Taken together, it is clear that increased expression of ANKHD1 is sufficient to sustain proliferation and growth [ 13 , 16 , 33 , 34 , 36 , 51 , 53 , 54 , 57 , 62 ] and to contribute to cellular invasion and metastasis [ 53 , 54 , 61 , 62 ] in multiple cancers.…”
Section: Role Of Ankhd1 In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, these proteins have been implicated in multiple functions, including proliferation, differentiation, cytoskeletal organization, and transcriptional control [141,[143][144][145]. Moreover, their dysregulation and role are increasingly recognized in the context of tumorigenesis/metastasis in various malignancies [139,143,144,[146][147][148]. Parallel discoveries in two laboratories have revealed that Mask binds Yorkie and acts as an important cofactor strongly potentiating the transcriptional activity of Yorkie and YAP [78,149].…”
Section: Maskmentioning
confidence: 99%